2018
DOI: 10.1053/j.gastro.2018.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mutations in Barrett’s Esophagus Before Progression to High-Grade Dysplasia or Adenocarcinoma

Abstract: In genomic analyses of BE tissues from patients with or without later progression to HGD or EAC, we found significantly higher numbers of TP53 mutations in BE from patients with subsequent progression. These mutations were frequently detected before the onset of dysplasia or substantial changes in copy number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
136
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(147 citation statements)
references
References 47 publications
(74 reference statements)
9
136
2
Order By: Relevance
“…In contrast to a previous NGS study, the high‐resolution SNP arrays used in our study permit highly sensitive detection of copy number alterations in small genomic regions, at exon resolution, and in small cellular subpopulations in each tested sample. The most frequent SCNAs in nondysplastic BE involved FHIT exon 5 and/or CDKN2A/B , and their combined alterations were significantly more prevalent in preprogression‐BE (88%) than in both NvDBE cohorts (24%).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In contrast to a previous NGS study, the high‐resolution SNP arrays used in our study permit highly sensitive detection of copy number alterations in small genomic regions, at exon resolution, and in small cellular subpopulations in each tested sample. The most frequent SCNAs in nondysplastic BE involved FHIT exon 5 and/or CDKN2A/B , and their combined alterations were significantly more prevalent in preprogression‐BE (88%) than in both NvDBE cohorts (24%).…”
Section: Discussionsupporting
confidence: 93%
“…Our data are consistent with previous studies showing frequent CDKN2A /p16 inactivation in EAC, preneoplastic BE and dysplastic precursor lesions . CDKN2A /p16 is a member of the INK4 family of cyclin‐dependent kinase inhibitor proteins (p16 INK4a , p15 INK4b , p18 INK4c and p19 INK4d ) that negatively regulate progression through the G1 phase of the cell cycle by binding to and inhibiting cyclin D/cdk4–6 complexes .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…BE is one of the precursors for EAC and has been extensively studied to identify early events of carcinogenesis and differences between the progressing and nonprogressing types of BEs. Some of these studies identified different mutation, DNA methylation, and SCNA patterns among the progressing and nonprogressing types of BE suggesting a window of opportunity for early detection with multiomics approach . A couple of recent reports using molecular biomarker‐based nonendoscopic method (Table ) enables an efficient, well‐tolerated, sensitive, and specific method of screening at‐risk populations for BE .…”
Section: Future Perspectivesmentioning
confidence: 99%